The compartmentalization of languages and identities among nationalist youth in Semarang - Tamtomo, Kristian (Wacana, Journal of the Humanities of Indonesia, 2018)
Contemporary mainstream discourse on youths in Indonesia tends to define it in terms of the popular-culture-oriented notion of youth. This article seeks to show that certain state-formed youth groups, particularly in institutional settings, continue to promote the state-oriented pemuda or nationalist youth identity. By looking at an example of a Paskibra group (Pasukan Pengibar Bendera – the Flag- Raising Troop) from a state vocational high school in Semarang, Central Java, the article seeks to highlight the way in which these youths combine language and symbolic behaviours to present this nationalist identity. Concurrently, these youths also appropriate elements of popular culture in order to present a compartmentalized or separate remaja identity that complements their core nationalist identity. While not prominently visible in Indonesian popular culture, nationalist forms of youth identity, such as the Paskibra, continue to have currency in various state and institutional sectors.